A victim of their own success? : employment and working conditions of academic staff in comparative perspective - Enders, Jürgen [Verfasser]; Teichler, Ulrich [Verfasser] (My University, 1997)
"Interest in the status and functions, the potential and the vulnerability of the academic profession has grown in recent times. International comparison is of special interest in this context: are the problems experienced more or les universal, or are there options and conditions in individual countries which might suggest solutions for the future? The paper analyses some findings and implications of the "International Survey of the Academic Profession" with a special focus on the various subgroups of academics in the European countries involved in this empirical study. The analyses focuses on the employment and working conditions, as well as the way academics handle their various professional tasks and functions. Considerable differences between the university professoriate, middle-rank and junior staff at universities and staff at other institutions of higher education are noted. At least in the majority of European countries surveyed, one would hesitate to consider them part of the same profession. By and large, however, the relatively independent nature of their jobs allows most academics to find areas of professional activity which are the source of professional attachment and satisfaction." (author's abstract, IAB-Doku) Der Artikel analysiert Befunde und Forderungen aus der Studie "International Survey of the Academic Profession", zur Beschäftigung und zu den Arbeitsbedingungen von Hochschullehrern in Ländern Europas, je nach Status und Hochschultyp heraus. (IAB)
Keywords: P 3.2.3 Lehrer; G 1.2.2.3 Beschäftigungsformen; G 2.3.2 Arbeits- & Beschäftigungsverhältnisse; G 2.3.1 Arbeitsteilung & -organisation; I 2.2.1 Westeuropa; I 2.3.2 Nordamerika; I 2.3.4 Asien; Lehrer; Hochschullehrer; Berufsproblem; Beschäftigung; Arbeitssituation; Hochschulpersonal; Internationaler Vergleich; Arbeitsbedingungen; Tätigkeitsmerkmal; Arbeitszufriedenheit; Niederlande; Schweden; Großbritannien; USA; Japan